Declining magnetic field at Maitri, Antarctica - Pathan, B.M.; Dhar, Ajay; Asinkar, R.L.; Selvamurugan, R.; Hanchinal, A.N. (My University, 2009)
The Earth's magnetic field is due to huge electric current circulating in the core of the Earth. Geomagnetic field is mostly dipolar in nature although multi poles also have some contribution. However, the main complication lies in the fact that there are a multitude of extraneous sources, which produce distortions in the magnetic field. As a consequence, the Earth¿s magnetic field is very complex which protects the Earth¿s surface and its inhabitants from hazardous cosmic radiation (energetic protons) received from the Sun. It is known that the Earth¿s magnetic field is decaying faster than any other worldwide geophysical phenomenon. This reported decrease is a major concern for the human kind. Will this continuous decrease lead to zero magnetic field sometimes in future? If so, how life on this planet will be affected? It is seen that the decline is mostly in the dipolar contribution. The decrease in magnetic field is not uniform all over the globe. It is reported that the geomagnetic field is declining in the Southern Hemisphere while in the Northern Hemisphere it is more or less steady or at a small increase. In the Southern Hemisphere too, the decrease is higher at certain locations. Indian Antarctic station, Maitri (Geog. 70.75o S, 11.75o E), is one such location recording a sharp decrease. Indian Institute of Geomagnetism is taking part in the annual Indian expeditions to Antarctica since its inception in 1981-82. A Proton Precession Magnetometer (PPM) is used to monitor the total magnetic field (F). It is seen that the magnetic field at Maitri has decreased by more than 2000 nT in the last 20 years. Geomagnetic field model reveals that the rate of decrease in the magnetic field at Maitri during the last century is about 105 nT/year. Maximum rate of decrease of about 120 nT/year is seen further north of this station. This result is discussed in terms of change of magnetic pole position, magnetic dipole moment and magnetic energy. It is seen that the decrease of energy in the dipole part has been, almost completely balanced by a corresponding increase in the energy of the non-dipole field. As a net result the energy of the total observed field measured all over the globe has remained almost constant. However, the magnetic moment has been found to change more rapidly at locations close to magnetic poles. Hence, the importance of continuous monitoring of total magnetic field at Maitri is emphasised.
Keywords: Geomagnetic field; Dakshin Gangotri; Maitri; Antarctica; Southern Hemisphere; Northern Hemisphere